Electroporation-enhanced transdermal diclofenac sodium delivery into the knee joint in a rat model of acute arthritis - Hartmann P; Butt E; Fehér Á; Szilágyi ÁL; Jász KD; Balázs B; Bakonyi M; Berkó S; Erős G; Boros M; Horváth G; Varga E; et al. (Dove Medical Press, 2018)
Petra Hartmann,1 Edina Butt,2 Ágnes Fehér,1 Ágnes Lilla Szilágyi,1 Kurszán Dávid Jász,1 Boglárka Balázs,3 Mónika Bakonyi,3 Szilvia Berkó,3 Gábor Erős,4 Mihály Boros,1 Gyöngyi Horváth,5 Endre Varga,2 Erzsébet Csányi3 1Institute of Surgical Research, University of Szeged, Szeged, Hungary; 2Department of Traumatology, University of Szeged, Szeged, Hungary; 3Department of Pharmaceutical Technology, University of Szeged, Szeged, Hungary; 4Department of Pathology, University of Szeged, Szeged, Hungary; 5Department of Physiology, University of Szeged, Szeged, Hungary Purpose: Since electroporation (EP) can increase the permeability of biological membranes, we hypothesized that it offers an opportunity to enhance the transdermal delivery of drugs for intra-articular indications. Our aim was to compare the anti-inflammatory and analgesic efficacy of EP-combined topical administration of diclofenac sodium hydrogel (50 mg mL-1 in 230 μL volume) with that of an equivalent dose of oral (75 mg kg-1) and simple topical administration. Methods: Arthritis was induced with the injection of 2% λ-carrageenan and 4% kaolin into the right knee joints of male Sprague Dawley rats. EP was applied for 8 min with 900 V high-voltage pulses for 5 ms followed by a 20 ms break. Drug penetration into the synovial fluid and plasma was detected by high-performance liquid chromatography. Leukocyte–endothelial interactions were visualized by intravital videomicroscopy on the internal surface of the synovium. Inflammation-induced thermal and mechanical hyperalgesia reactions, knee joint edema, and inflammatory enzyme activities were assessed at 24 and 48 h after arthritis induction. Results: EP significantly increased the plasma level of diclofenac as compared with the topical controls 10 min after the 2% λ-carrageenan and 4% kaolin injection. Increased leukocyte–endothelial interactions were accompanied by joint inflammation, which was significantly reduced by oral and EP diclofenac (by 45% and by 30%, respectively) and only slightly ameliorated by simple topical diclofenac treatment (by 18%). The arthritis-related secondary hyperalgesic reactions were significantly ameliorated by oral and EP-enhanced topical diclofenac treatments. The knee cross-section area (which increased by 35%) was also reduced with both approaches. However, simple topical application did not influence the development of joint edema and secondary hyperalgesia. Conclusion: The study provides evidence for the first time of the potent anti-inflammatory and analgesic effects of EP-enhanced topical diclofenac during arthritis. The therapeutic benefit provided by EP is comparable with that of oral diclofenac; EP is a useful alternative to conventional routes of administration. Keywords: diclofenac, transdermal delivery, HPLC, intravital videomicroscopy